(3SjQI QShd Gddg Udi Gddg Ydjg hSdes - (3GHf gTGe , YHO Gdedc Hf gTGe Hf GjhH GdMejQj GdeYGaQj, LeGd GdOjf CHh eMeO,J (B213 (3g` s
(3ChdgG (B:s
(3gPG cJGH SjQI QShd Gddg Udi Gddg Ydjg hSde eMeO Hf YHO Gddg Hf YHO GdeWdH hGSe YHO GdeWdHi SjHI Hf gTGe s
(3BNQgG (B:s
(3ef bUjOI dMGeO Hf KGHJ QVi Gddg Yfg jQKi QShd Gddg Udi Gddg Ydjg hSde jG CaVd GdfGS Efi cfJ ai fgQ CUHMJ efg ceKd GdeaQO GdUGOi s
(3QhGjI Yf eMeO Hf ESMGb Hf jSGQ GdeWdHi (B- (3QhGjI RjGO Hf YHO Gddg GdcHGFi GdfSNi ai YTQjf LRA GJLRFI bOjeIs
(3hHChdgG hBNQgG bQGBJ efbhdg Yf GdCUd GdefJSN efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JaSjQ s
Keywords: (3GdJGQjNs